2007
DOI: 10.1152/ajpgi.00417.2006
|View full text |Cite
|
Sign up to set email alerts
|

fMLP induces Hsp27 expression, attenuates NF-κB activation, and confers intestinal epithelial cell protection

Abstract: Sustained expression of cytoprotective intestinal epithelial heat shock proteins (Hsps), particularly Hsp27, depends on stimuli derived from bacterial flora. In this study, we examined the role of the bacterial chemotactic peptide fMLP in stimulating colonic epithelial Hsp expression at concentrations encountered in a physiological milieu. Treatment of the polarized human intestinal epithelial cell line Caco2bbe with physiological concentrations of fMLP (10-100 nM) induced expression of Hsp27, but not Hsp72, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 54 publications
(51 reference statements)
1
26
0
1
Order By: Relevance
“…Moreover, we demonstrated that restoration of miR-193a-3p reduced PepT1 expression and transport activity, which subsequently decreased the activation of the NF-B signaling pathway and led to the suppression of fMLF triggered inflammation in Caco2 cells. Several studies have indicated that fMLF could stimulate a time-dependent increase of IB-␣ phosphorylation in the intestinal epithelial cells, and the NF-B pathway may play a role in the synergistic activation of intestinal immune response induced by fMLF (36,37). Activation of the NF-B pathway could be induced by IB kinase and ubiquitination of the NF-B essential modulator, which subsequently activates NOD2 by muramyl-dipeptide, which derives from peptidoglycan of bacteria (38).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we demonstrated that restoration of miR-193a-3p reduced PepT1 expression and transport activity, which subsequently decreased the activation of the NF-B signaling pathway and led to the suppression of fMLF triggered inflammation in Caco2 cells. Several studies have indicated that fMLF could stimulate a time-dependent increase of IB-␣ phosphorylation in the intestinal epithelial cells, and the NF-B pathway may play a role in the synergistic activation of intestinal immune response induced by fMLF (36,37). Activation of the NF-B pathway could be induced by IB kinase and ubiquitination of the NF-B essential modulator, which subsequently activates NOD2 by muramyl-dipeptide, which derives from peptidoglycan of bacteria (38).…”
Section: Discussionmentioning
confidence: 99%
“…Hsp25 and Hsp72 have been shown to reduce NF-B activation (4,22,55), which is central to the expression of several proinflammatory cytokines (23). While exercise can acutely activate NF-B (17,21), chronic activation of this pathway has been associated with muscle weakness (3) and contractile protein loss (28,30).…”
Section: Discussionmentioning
confidence: 99%
“…Inducible HSP-dependent inhibition of the NFjB pathway has also been documented in GECs. 27,28 The underlying mechanisms could involve activation of IjBa gene expression and inhibition of phosphorylation and degradation of IjBa protein. Conversely, HSP27 is implicated in NF-jB activation by reactive oxygen species.…”
Section: Regulation Of Immune Responses and Inflammationmentioning
confidence: 99%